Emission and dispersion modelling of Lisbon air quality at local scale - Borrego, C.
The main objective of the paper is the study of air pollution in Lisbon city at local scale through the application of the modelling system developed at the University of Aveiro, linking two numerical tools: (i) the Transport Emission Model for Line Sources (TREM) and (ii) the Local Scale Dispersion Model (VADIS). Furthermore, analysis of the modelling system performance from the point of view of Quality Objectives established by the new European Legislation is one of the principal goals of the present work. TREM is designed to support quantification of emissions induced by road traffic. The emission rate is estimated as a function of average speed. Different technologies (engine type, model year) and engine capacities are distinguished. The model is particularly designed for line sources and is implemented in a Geographical Information System. VADIS is an integrated system, coupling a boundary layer flow module with a Lagrangian dispersion module, which was adapted to the simulation of urban air pollution, mainly in street canyon dispersion conditions. This model has the capability to support multi-obstacle and multi-source description, as well as time varying flow fields and time varying emissions. The modelling system TREM/VADIS was applied to the Lisbon downtown area and results concerning carbon monoxide concentration values are presented and analysed. Also, a comparison of simulated and measured data using European legislation criteria is discussed. This numerical tool has demonstrated a satisfactory performance to calculate the flow and dispersion around obstacles under variable wind conditions, providing important information to be used by decision-makers for air quality assessment.